Osmotic oedometer using sodium chloride solution and reverse osmosis membrane - Bulolo, Sam (2021)
There are two suction application techniques in laboratory testing of unsaturated soils: (1) the axis-translation technique in which pore-air pressure is elevated above atmospheric pressure and pore-water pressure is at an atmospheric or a small positive value to give a matric suction and (2) using salt solutions. Salt solutions can be used to control the relative humidity of the air surrounding the soil specimen in the vapor equilibrium technique or as an osmotic suction applied through a semipermeable membrane in the osmotic technique. The salt solution in the vapor equilibrium technique applies a total suction, whereas the salt solution in the osmotic technique induces a matric suction on the soil specimen. Unlike the axis-translation technique and vapor equilibrium technique, the osmotic technique does not require a sealed chamber, but it is not as popular as the axis-translation technique and vapor equilibrium technique because the commonly used poly(ethylene glycol) solution and cellulosic membrane are susceptible to degradation during long-duration tests. This paper investigates the osmotic technique using sodium chloride solutions and a reverse osmosis membrane in a conventional oedometer. The performance of the updated osmotic oedometer was evaluated using kaolin–bentonite specimens. A kaolin–bentonite specimen was first mechanically consolidated, and thereafter the water within the base of the oedometer was replaced with sodium chloride solution. The results show that osmotic technique causes the soil specimen to be compressed further. However, the measured matric suction of the soil specimen at equilibrium is less than the applied suction. The difference is attributed to the membrane resistance effect. The updated osmotic oedometer is attractive, as it eliminates the drawbacks of the previous osmotic oedometer, and it can theoretically apply matric suction as high as 5,000 kPa.